Respostas
respondido por:
3
x+y=10
2x+y=7
x=10-y
20-2y+y=7
-y=7-20
-y=13
y=13
x+13=10
x=10-13
x=-3
respondido por:
0
olá.
x+y=10
2x+y=7
x=10-y
2x+y=7
↓
2·10-y+y=7
2y+20+y=11
2y+20+y=11
2y+y=11-20
3x=-9
x=-9/3
x=-3
-3·7=13
y=13
espero ter te ajudado
bons estudos
=D
x+y=10
2x+y=7
x=10-y
2x+y=7
↓
2·10-y+y=7
2y+20+y=11
2y+20+y=11
2y+y=11-20
3x=-9
x=-9/3
x=-3
-3·7=13
y=13
espero ter te ajudado
bons estudos
=D
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás